Editorial Introduction - Gordon Wells (Networks: An Online Journal for Teacher Research, 1999)
This issue sees a continuation of a strand, begun in the first issue, of articles written by collaborative groups of educators who span the school-university divide. As the authors of all these articles note, when school-based practitioners or preservice teachers in their practicums work together with colleagues in universities they create a synergy that makes ripples - or even waves - beyond their individual classrooms. As they present their work at local or national conferences and publish in venues such as Networks, the value of their work is recognized by others, who are inspired to adopt and adapt their ideas to suit their own local situations.